A consideração de diferentes formas de distribuição do carregamento vertical em projetos estruturais de alvenaria estrutural: estudo de caso dos efeitos de uma obra com blocos de concreto - Gibbert, Fernando André (2012)
To be a balance between security and economy is necessary to evaluate different types of sizing for structural masonry, where the elements that support the loads of the structure are the walls formed by structural blocks. The calculations improvement becomes necessary due to the gradual increase in demand of structural masonry projects, which is becoming a greater number of floors. In this work is performed an analysis of the results in sizing by compression, shear and and flexocompression, according to NBR 15961-1 (2011) considering: the calculation procedures for vertical loads distribution on insulated walls, in groups of insulated walls and groups of walls with interaction. The goal is to provide information about the influence of each method in the resistance of the blocks, the need to use grout and inserting steel bars. Taking into account these procedures, it is found that one performed with groups of walls with interaction was more economical. However, the procedure with insulated walls resulted in safer. Evaluating the aspects of economy and security, is necessary to adopt a procedure that proves viable, at both points and thus appears as an intermediate factor between these two results. Therefore by the analyzes and studies of the procedures mentioned, it is suggested to adopt to the implementation, the considerations of calculation of groups with insulated walls